Eksposure Condition Pada Self-Healing Beton Yang Korosi Menggunakan NDT Method: Analisis Bibliometric - Fajrina, Nur; Zaki, Ahmad (Universitas Andalas, 2024)
Research related to the evaluation of concrete under exposure conditions or high temperature exposure has been conducted by several researchers. However, research evaluating bacterial concrete on corrosion with temperature exposure using non-destructive testing (NDT) methods is very limited. This article is a literature review that focuses on publications discussing bacterial concrete, corrosion, temperature exposure, and NDT. This study aims to describe the visual relationship and research gap in the field of bacterial concrete on temperature exposure to corrosion using the NDT method in the last decade (2013-2023). The search method used in this article is using the Vos Viewer application from the Scopus database (scopus.com) with a total of 140 publications. The types of analysis carried out are annual publication trends per country, developments in the number of annual publications, keyword grouping, and author grouping. The results of this study are expected to explain the research gap and be an important reference for researchers who study similar issues.